Design and Analysis of Effects of Triplet Repeat Oligonucleotides in Cell Models for Myotonic Dystrophy - Anchel González-Barriga; Susan AM Mulders; Jeroen van de Giessen; Jeroen D Hooijer; Suzanne Bijl; Ingeborg DG van Kessel; Josee van Beers; Judith CT van Deutekom; Jack AM Fransen; Bé Wieringa; Derick G Wansink (Molecular Therapy: Nucleic Acids, 2013)
Myotonic dystrophy type 1 (DM1) is caused by DM protein kinase (DMPK) transcripts containing an expanded (CUG)n repeat. Antisense oligonucleotide (AON)-mediated suppression of these mutant RNAs is considered a promising therapeutic strategy for this severe disorder. Earlier, we identified a 2′-O-methyl (2′-OMe) phosphorothioate (PT)–modified (CAG)7 oligo (PS58), which selectively silences mutant DMPK transcripts through recognition of the abnormally long (CUG)n tract. We present here a comprehensive collection of triplet repeat AONs and found that oligo length and nucleotide chemistry are important determinants for activity. For significant reduction of expanded DMPK mRNAs, a minimal length of five triplets was required. 2′-O,4′-C-ethylene-bridged nucleic acid (ENA)–modified AONs appeared not effective, probably due to lack of nuclear internalization. Selectivity for products from the expanded DMPK allele in patient myoblasts, an important requirement to minimize unwanted side effects, appeared also dependent on AON chemistry. In particular, RNase-H–dependent (CAG)n AONs did not show (CUG)n length specificity. We provide evidence that degradation of long DMPK transcripts induced by PS58-type AONs is an RNase-H independent process, does not involve oligo-intrinsic RNase activity nor does it interfere with splicing of DMPK transcripts. Our collection of triplet repeat AONs forms an important resource for further development of a safe therapy for DM1 and other unstable microsatellite diseases.